Effect of Gd Doping on Ni Bead Nanoparticles for Enhanced Pharmaceutical Degradation - Norezatul Shahirah Ahmad Zamanhuri; Norzahir Sapawe; Siti Fatimah Ibrahim; Lusi Ernawati; Bernard Maringgal; Daniel Joe Dailin (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The presence of pharmaceutical pollutants, including theophylline, in the environment presents considerable risks owing to their persistence and toxicity. This research examines the improvement of photocatalytic degradation of theophylline using gadolinium (Gd) doped nickel (Ni) bead nanoparticles. The objectives encompass the synthesis of Gd-Ni nanoparticles and the assessment of their photocatalytic efficiency under different conditions. Gd-Ni nanoparticle beads were synthesized using precipitation and sol-gel techniques. The evaluation of photocatalytic performance involved measuring the degradation rates of theophylline when exposed to UV light. The results demonstrated that the best conditions for photocatalytic activity were achieved at a neutral pH of 7, with a catalyst dosage of 20 g and an initial concentration of 10 ppm of theophylline. The 5 % Gd-Ni bead nanoparticles exhibited a degradation efficiency of 88.571 % within four hours of irradiation, surpassing the 83.758 % removal achieved by the 3 % Gd-Ni bead nanoparticles. The findings demonstrate the efficacy of Gd-doped Ni bead nanoparticles as photocatalysts for the sustainable elimination of pharmaceutical pollutants, thereby aiding environmental remediation initiatives.